2021
DOI: 10.4103/aja.aja_84_20
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal fertilization in ICSI and its association with abnormal semen parameters

Abstract: Intracytoplasmic sperm injection (ICSI) efficiently addresses male factor infertility. However, the occurrence of abnormal fertilization, mainly characterized by abnormal pronuclei (PN) patterns, merits investigation. To investigate abnormal fertilization patterns following ICSI and identify their respective associations with abnormal parameters in semen analysis (SA), a retrospective observational study including 1855 cycles was performed. Male infertility diagnosis relied on the 2010 WHO criteria. The popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…No correlation was observed between the semen analysis abnormalities and the 3PN formation rates in ICSI [21]. Some studies suggest severe sperm abnormalities and oocyte aging can contribute to the process [4,22].…”
Section: Discussionmentioning
confidence: 87%
“…No correlation was observed between the semen analysis abnormalities and the 3PN formation rates in ICSI [21]. Some studies suggest severe sperm abnormalities and oocyte aging can contribute to the process [4,22].…”
Section: Discussionmentioning
confidence: 87%
“…The semen sample may show a low number of sperm and abnormal morphology, and these sperm are incapable of penetrating the egg's membranes. This is often associated with a high percentage of abnormally shaped sperm (morphology) [20]. In severe cases, sperm abnormality may result in total failure of fertilization.…”
Section: No Pronuclear (0pn) Oocytesmentioning
confidence: 99%
“…Many genetic factors have been implicated in male infertility, and prior studies have consistently demonstrated that individuals experiencing severe oligozoospermia (i.e., low sperm count) and teratozoospermia (i.e., abnormal sperm forms) have a higher incidence of sperm aneuploidy than those with normal semen parameters [8][9][10][11]. Recent observational studies have revealed a possible association between abnormal semen parameters and impaired fertilization rates and embryonic development, even after IVF/ICSI [12]. An emerging concern is the potential link between these conditions and an increased risk of aneuploidy in sperm and embryos.…”
Section: Introductionmentioning
confidence: 99%